2021
DOI: 10.1038/s41587-021-00933-4
|View full text |Cite
|
Sign up to set email alerts
|

In vivo adenine base editing of PCSK9 in macaques reduces LDL cholesterol levels

Abstract: Most known pathogenic point mutations in humans are C•G to T•A substitutions, which can be directly repaired by adenine base editors (ABEs). In this study, we investigated the efficacy and safety of ABEs in the livers of mice and cynomolgus macaques for the reduction of blood low-density lipoprotein (LDL) levels. Lipid nanoparticle–based delivery of mRNA encoding an ABE and a single-guide RNA targeting PCSK9, a negative regulator of LDL, induced up to 67% editing (on average, 61%) in mice and up to 34% editing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
203
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(212 citation statements)
references
References 71 publications
6
203
0
3
Order By: Relevance
“…Even though the first clinical trials have reported an effective clinical benefit, long term studies are yet to be conducted to assess the safety and efficacy [163]. Furthermore, adenine base editors and CRISPR adenine base editors can be used to insert a splice site mutation in the PCSK9 gene to inhibit and knockdown PCSK9 for therapeutic applications [164,165]. This has already been studied in mouse and macaque models, in order to report that this method can be fitting to treat patients with familial hypercholesterolaemia in the future [164].…”
Section: Pcsk9 Activators/inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the first clinical trials have reported an effective clinical benefit, long term studies are yet to be conducted to assess the safety and efficacy [163]. Furthermore, adenine base editors and CRISPR adenine base editors can be used to insert a splice site mutation in the PCSK9 gene to inhibit and knockdown PCSK9 for therapeutic applications [164,165]. This has already been studied in mouse and macaque models, in order to report that this method can be fitting to treat patients with familial hypercholesterolaemia in the future [164].…”
Section: Pcsk9 Activators/inhibitorsmentioning
confidence: 99%
“…Furthermore, adenine base editors and CRISPR adenine base editors can be used to insert a splice site mutation in the PCSK9 gene to inhibit and knockdown PCSK9 for therapeutic applications [164,165]. This has already been studied in mouse and macaque models, in order to report that this method can be fitting to treat patients with familial hypercholesterolaemia in the future [164]. PCSK9 expression can also be affected and controlled by influencing various factors involved in its production, like transcription factors.…”
Section: Pcsk9 Activators/inhibitorsmentioning
confidence: 99%
“…1b ). mRNA can be used to replace protein, using replacement therapies 57 ; to reduce protein levels, using Cas9 cutting approaches 58 ; or to repair protein mutations at the DNA level, using base editing 59 , 60 . In 2021, researchers reported the successful use of LNPs encapsulating Streptococcus pyogenes Cas9 (CRISPR-associated endonuclease Cas9) mRNA and a CRISPR guide RNA in six patients with hATTR amyloidosis with polyneuropathy; a single 0.3 mg/kg dose resulted in a mean reduction from baseline of blood transthyretin (TTR) levels of 87% at 28 days post-dose 58 .…”
Section: Therapeutic Rna Payloadsmentioning
confidence: 99%
“…Newer lipids reported, such as LP01 77 (Intellia Therapeutics), Lipid H 128 (Moderna), and FTT5 103 (Ohio State and Beam Therapeutics), have also delivered mRNA to the mouse liver. Recently, two LNPs formulated with an unreported cationic or ionizable lipid, PEG-lipid, cholesterol and 1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC) delivered mRNA encoding a base-editing Cas9 and sgRNA targeting PCSK9 to the liver in non-human primates 59 , 60 . A single LNP administration led to months of sustained PCSK9 silencing.…”
Section: Synthetic Vehicles For Rna Deliverymentioning
confidence: 99%
“…Noteworthy, a different approach to inhibit PCSK9 synthesis may originate from base editors applied to make precise single-nucleotide changes. Actually, new gene-editing technologies are becoming promising tools for future therapeutic applications, also in the management of hypercholesterolemia by targeting PCSK9 [170,171].…”
Section: Current Drugs To Inhibit Pcsk9mentioning
confidence: 99%